Evaluation of heat shock protein 70 kDa in plasma of patients with active infective valve endocarditis - A. A. Krikunov; A. B. Koltunova; E. Y. Bespalova; A. V. Petkov; F. A. Pristavka; S. P. Spysarenko; T. A. Malysheva (Ukrainian Journal of Cardiovascular Surgery, 2016)
Development of infective endocarditis initiates a complex immunological response of the organism changing in time: the prevalence of pro-and anti-inflammatory mechanisms at the beginning is replaced by immunosuppression. A significant role in antigen presentation, cross-presentation, activation of macrophages and lymphocytes play the heat shock proteins (HSP). HSP provide a link between innate and adaptive immunity. The study included 18 patients with active infective valve endocarditis operated from 01.01.2010 по 31.12.2011yy. Assessment of the relationship between clinical characteristics of patients with infective endocarditis and the initial level of heat shock protein 70 kDa was performed. Patients with the presence of signs of chronic persistent infection and catabolism were characterized by high levels of heat shock proteins 70 kDa. The presence of high levels of heat shock proteins 70 kDa indicated the depression of cellular and humoral immunity. These results confirm the development of the syndrome of persistent inflammation, immunosuppression and catabolism in patients with infective endocarditis.